The Degree of Arabic Language Teachers' Performance in Reinforcing Cooperative and Community Involvement Skills among Secondary Stage Students in Madinah - Al-Dosari, Mashael Saleh Saad; Al-Ruwaythi, Reem Mahal Hamdy (Journal of Educational and Psychological Sciences, 2024)
The current research aims to identify the performance level of Arabic language teachers in enhancing cooperation and community participation skills among female high school students in Al-Madinah Al-Munawwarah. The researchers adopted a descriptive approach with a survey style. The instrument used was an observation card developed by the researchers, consisting of 20 indicators distributed across (3) axes. The research sample comprised 30 Arabic language teachers from secondary schools in Al-Madinah Al-Munawwarah. The research found that the performance level of Arabic language teachers in enhancing cooperation and community participation skills among female high school students obtained an average score of (1.87), indicating a moderate level. Regarding the axes, cooperative work came first with an average score of (2.08), followed by social relationship management (2.05), both at a moderate level. Voluntary work came third with a score of (1.48), indicating a weak level. Based on the results, the researchers recommended the necessity of conducting training courses for Arabic language teachers to enhance their teaching performance in promoting cooperation and community participation skills. They also suggested attempts to alleviate the workload assigned to Arabic language teachers and proposed conducting a study aimed at identifying the challenges facing Arabic language teachers in promoting cooperation and community participation skills among female high school students.
Keywords: Teacher's performance; Arabic language teachers; Cooperative and community Involvement Skills